Designing Pocket Park at Dense Building Area with Micro Climate Approach - Ariani, Rindy; Fitri, Rahmadhani; Wisdianti, Dara (Indonesian Journal Publisher, 2024)
Pocket parks can create new public spaces without needing large-scale redevelopment, usually smaller than one hectare and created in densely developed urban areas. This research aims to improve the community's standard of living, creating a more comfortable environment for humans and the environment. This research focuses on the design of pocket parks in dense building areas with the concept of microclimate. Data is collected from field observations. The design results are expected to provide an understanding of the role of pocket parks in dense neighborhoods and guide future park planning and management.